ADVANTAGES OF USING GAME TECHNOLOGIES IN ENGLISH TEACHING - Urokova Sevinch (Journal of new century innovations, 2023)
Abstract: This article is about teaching English as a Second Language (ESL) through the games in classes 6 to 9. It is very important to carry out activities in the target language, in this case, English. Here is given many different kinds of warming up activities to teach foreign language lessons and make them more beneficial and effective